Antibacterial Activity of Zanthoxylum acanthopodium DC. Extract Against Staphylococcus aureus: An In Vitro Study: Antibacterial Activity of Zanthoxylum acanthopodium DC - Gostry Aldica Dohude; Ahyar Riza; Hendry Rusdy; Ribka Ulina Ritonga (Journal of Syiah Kuala Dentistry Society, 2025)
Dry socket is an acute inflammation of the alveolar bone around an extracted tooth due to the detachment of a blood clot. Staphylococcus aureus is one of the bacteria that plays a role in dry socket occurrence. Andaliman fruit (Zanthoxylum acanthopodium DC.) contains alkaloids, flavonoids, tannins, and triterpenoids/steroids that have potential as antibacterials. This study aims to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of andaliman fruit extract against Staphylococcus aureus in vitro. This type of research is a laboratory experiment with a post-test-only control group design. The andaliman fruit extract was made using maceration extraction. The antibacterial effectiveness test used the dilution method with 4 samples for each treatment. The samples consisted of seven treatment groups, namely andaliman fruit extract concentrations of 50%, 25%, 12.5%, 6.25%, 3.125%, positive control (Chlorhexidine gluconate 0.2%), and negative control (DMSO). MIC was determined by observing the turbidity of the solution while MBC was determined by counting the number of colonies that grew on agar media. he results showed that the 3.125% concentration of andaliman fruit extract was the first clear solution compared to the negative control. The number of colonies that grew in andaliman fruit extract concentrations of 50%, 25%, 12.5%, 6.25%, 3.125% was 111.50±16.010 CFU/mL; 266.50±15.588 CFU/mL; 369.75±38.266 CFU/mL; 489.75±49.688 CFU/mL; and 744.75±14.033 CFU/mL. Data were analyzed using the Kruskal-Wallis test which showed a p-value of 0.000. The andaliman fruit extract is effective as an antibacterial against Staphylococcus aureus with MIC 3.125% while MBC was not found